A Lactate Kinetics Method for Assessing the Maximal Lactate Steady State Workload - Hering, Gernot O.; Hennig, Ewald M.; Riehle, Hartmut J.; Stepan, Jens (Frontiers in Physiology, 2018)
During a continuously increasing exercise workload (WL) a point will be reached at which arterial lactate accumulates rapidly. This so-called lactate threshold (LT) is associated with the maximal lactate steady state workload (MLSSW), the highest WL, at which arterial lactate concentration [LA] does not change. However, the physiological range in which the LT and the MLSSW occur has not been demonstrated directly. We used minor WL variations in the MLSSW range to assess arterial lactate kinetics in 278 treadmill and 148 bicycle ergometer exercise tests. At a certain workload, minimal further increment of running speed (0.1 - 0.15 m/s) or cycling power (7 - 10 W) caused a steep elevation of [LA] (0.9 ± 0.43 mM, maximum increase 2.4 Mm), indicating LT achievement. This sharp [LA] increase was more pronounced when higher WL increments were used (0.1 vs. 0.30 m/s, P = 0.02; 0.15 vs. 0.30 m/s, P < 0.001; 7 vs. 15 W, P = 0.002; 10 vs. 15 W, P = 0.001). A subsequent workload reduction (0.1 m/s / 7 W) stopped the [LA] increase indicating MLSSW realization. LT based determination of running speed (MLSSW) was highly reproducible on a day-to-day basis (r = 0.996, P < 0.001), valid in a 10km constant velocity setting (r = 0.981, P < 0.001) and a half marathon race (r = 0.969, P < 0.001). These results demonstrate a fine-tuned regulation of exercise-related lactate metabolism, which can be reliably captured by assessing lactate kinetics at the MLSSW.